A DESIGN UI/UX E-LEARNING ENGLISH MOBILE USING USER CENTERED DESIGN (UCD) METHOD: English - Alamsyah, Dwi Rizky; Resmi, Mochzen Gito; jaelani, Irsan (Sinkron : jurnal dan penelitian teknik informatika, 2023)
E-learning English Mobile application design is a Mobile-based application design needed by SMAN 2 Purwakarta for future learning purposes. With this application design SMAN 2 Purwakarta has a picture of learning applications that will facilitate students and teachers in learning and teaching activities. In this application design research, there are several methods that are widely used by previous researchers. One of the methods used in this research is the User Centered Design (UCD) method which is a new method in system development. UCD is a language that is widely applied in describing designs. The concept of UCD is the user as the center of the system development process, and the goals, the system environment are all based on the user experience. The results of this study produced a learning application prototype, namely E-learning English Mobile. After testing using the System Usability Scale (SUS). The average value obtained is 78. It can be concluded that the design of the E-Learning English Mobile application is acceptable because it meets the Acceptable category